THE WORKING CAPITAL, INVESTMENT, THIRD PARTY FUND ON OUTSTANDING FINTECH WITH CREDITOR GROWTH AS MODERATOR - Rinofah, Risal; Sari, Pristin Prima; Pratama, Yhoga Heru; Trinugroho, Irwan (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
The research aims to empirically examine the influence of working capital financing, investment and third party funds on Fintech Outstanding with Credit Growth Moderators in 2020-2023. Multiple Linear Regression Method with SPSS IBM 20 analysis tool. The significance level of the accepted research hypothesis is 5%. The research sample uses data from the My Data application in Yogyakarta online from the OJK. The benefit of the research is that investors can consider investing in Fintech Lending companies, for Fintech Company management it is to consider flexibility in credit conditions for MSMEs to increase Fintech Outstanding. The results of the research are that working capital credit has a significant effect on outstanding fintech but investment credit, deposits and creditor growth do not have a significant effect on outstanding fintech. Creditor growth was unable to significantly moderate working capital and investment in outstanding fintech. Keywords : Creditor, Fintech, Investment, Third Party fund, Working Capital.